"Cell identity" crisis: Another call for immediate action. Issue 1 (10th October 2016) - Elgui de Oliveira, Deilson; Marques, Cleiton Silva; Losi, Victor Costa
Abstract : Comment on: J. Wei, J. Zhang, Y. Si, M. Kanada, Z. Zhang, S. Terakawa, H. Watanabe, Blockage of LMP1-modulated store-operated Ca(2+) entry reduces metastatic potential in nasopharyngeal carcinoma cell, Cancer Lett. 360 (2015) 234–244. doi:10.1016/j.canlet.2015.02.032